Formulasi Sediaan Permen Jahe (Zinger Officinale) Dari Hasil Budidaya Tanaman Obat Keluarga (TOGA) sebagai Antioksidan - Ovalina Sylvia Br. Ginting; Robiatun Rambe; Riezky Chairunnisa (Journal of Pharmaceutical and Sciences, 2023)
There are many natural sources of antioxidants in food, one of which is ginger. Ginger (Zinger officinale var.rubrum) is a spice plant that is rich in antioxidants originating from South Asia, and has now spread throughout the world. research shows that some people do not like ginger rhizome directly because commercial ginger candy has a very spicy taste and the vitamin C content is still low at around 10.675 mg/100g. this research increases the content of antioxidants (vitamin C) and minimizes the spicy taste of ginger extract jelly candy. This research is a type of experimental research. The parameters observed in this study were organoleptic tests consisting of hedonic tests (preferences) and analysis of proximate nutritional content (moisture content, ash content, reducing sugar content) and vitamin C levels in the best formula jelly candy. The results obtained by the panelists' organoleptic assessment preferred the color of ginger candy in the P3 treatment with the highest percentage of 100%. The results of the hedonic test on ginger candy were carried out on 25 panelists, the highest percentage of acceptance was found in ginger candy P3, namely 100%. Laboratory analysis results on P3 ginger candy include proximate analysis (moisture content, ash content, reducing sugar content) and vitamin C levels